2011
DOI: 10.2174/1874285801105010055
|View full text |Cite
|
Sign up to set email alerts
|

Subpathotypes of Avian Pathogenic Escherichia coli (APEC) Exist as Defined by their Syndromes and Virulence Traits

Abstract: Avian pathogenic Escherichia coli (APEC) strains cause different types of systemic extraintestinal infections in poultry, collectively termed colibacillosis, which can cause significant economic losses in the poultry industry. To date, there have been no descriptions of genes or characteristics that allow for the classification of avian strains pathotypes responsible for causing specific diseases in their hosts. In this study we aimed to characterize avian E. coli strains representing 4 groups, including one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
3
14
0
1
Order By: Relevance
“…The phylogenetic analysis, also demonstrated, as indicated by the MLST study, that APEC strains are not a homogeneous group. Thus, the phylogenetic tree and virulence gene profiles revealed that the strains are very diverse, corroborating previous works (Maturana et al 2011, Schouler et al 2012. For strain S17, a septicaemic Brazilian APEC, both methodologies clearly showed that it has a closer genetic similarity with strain H10407, a human ETEC strain.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The phylogenetic analysis, also demonstrated, as indicated by the MLST study, that APEC strains are not a homogeneous group. Thus, the phylogenetic tree and virulence gene profiles revealed that the strains are very diverse, corroborating previous works (Maturana et al 2011, Schouler et al 2012. For strain S17, a septicaemic Brazilian APEC, both methodologies clearly showed that it has a closer genetic similarity with strain H10407, a human ETEC strain.…”
Section: Discussionsupporting
confidence: 87%
“…However, the high diversity encountered in E. coli species difficult the use of a single set of virulence factors for diagnosis (Schouler et al 2012). For Brazilian APEC strains, a recent study of our group, showed that the analysis of several biological characteristics, such as adhesion to eukaryotic cell cultures, pathogenicity levels according to the lethal dose (50%) assay, phylogenetic groups and virulence gene profiles, indicated that APEC strains could be organized into a structured set of subgroups associated with specific infectious syndromes (Maturana et al 2011). These finds demonstrated that APEC strains are very diverse and that the detection of specific genes is not sufficient to define this group.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VGs reported in this study are similar to a number of overseas studies, which have reported variation in VG frequency and combinations in CEC and FEC isolates (Johnson et al, 2008b;Lynne et al, 2012;Maturana et al, 2011;Olsen et al, 2012;Rodriguez-Siek et al, 2005a). …”
Section: Discussionsupporting
confidence: 89%
“…An interesting hypothesis generated out of the Nolan laboratory suggests that, although there are many disease presentations possibly arising through the expression of many combinations of virulence determinants, perhaps there exists a minimal set of genes that define APEC [18]. Maturana et al (2011) used PCR to detect APEC virulence genes including yjaA, tspE4.C2, iucA, irp-2, fepC, crl, csgA, tsh, lpfAO141, lpfAO154, iha, sitA, fyuA, fimA, papA of which crl, csgA, lpfAO141, lpfAO154, fimA, papA and concluded that not all APEC strains have all determinants and different combinations of determinants in a strain will contribute to pathogenic potential [19]. …”
Section: Introductionmentioning
confidence: 99%